PERAN METODE PENDIDIKAN QUR’ANI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR: STUDI LITERATUR - Siti Nabila Nur Annisa; M. Ilmil Zawawi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the role of Qur’anic educational methods in improving the quality of Islamic Religious Education (PAI) learning at the elementary school level. The problem addressed in this research is the dominance of conventional teaching methods, particularly lectures, which tend to limit student engagement and reduce learning effectiveness. The objective of this study is to analyze various Qur’anic educational methods and explore their relevance in enhancing the quality of PAI learning. This research employs a qualitative approach using a library research design. Data sources consist of primary data from the Qur’an and secondary data from relevant scholarly literature such as books, journal articles, and previous studies. Data were collected through documentation techniques and analyzed using content analysis to identify key themes related to Qur’anic teaching methods and their application in elementary education. The findings indicate that Qur’anic educational methods such as dialogue (hiwar), exemplary behavior (uswah), storytelling (qishash), parables (amtsal), and motivation and warning (targhib and tarhib)—are highly relevant and effective in fostering interactive, meaningful, and student-centered learning. These methods not only enhance cognitive understanding but also contribute significantly to the development of students’ moral and spiritual character. The study concludes that the systematic and contextual integration of Qur’anic methods can improve both learning outcomes and character formation, provided that teachers possess adequate pedagogical competence and are supported by a conducive learning environment.